2005
DOI: 10.1111/j.1651-2227.2005.tb01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bilirubin and phototherapy on osmotic fragility and haematoporphyrin‐induced photohaemolysis of normal erythrocytes and spherocytes

Abstract: Aim: To study the effects of phototherapy on erythrocyte haemolysis in vitro and to determine possible differences in sensitivity to phototherapy between normal erythrocytes and spherocytes. Methods: Erythrocytes from four normal healthy donors and two donors with hereditary spherocytosis were treated with bilirubin (160 μM) in the presence of human serum albumin in the molecular ratio bilirubin/albumin 0.8. Treated cells were maintained either in the dark or in blue light (450 nm, 8 mW/cm2, 30 min). The exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…Failure of phototherapy to be effective in reducing TSB levels in some infants with hereditary spherocytosis and hyperbilirubinemia has been hypothesized to be due to increased hemolysis from the absorption of light and photosensitization of cell membrane contents. In an in vitro study using RBCs from healthy donors and patients with hereditary spherocytosis, the investigators showed that the osmotic fragility of normal RBCs was increased in the presence of bilirubin or bilirubin and phototherapy 5. Phototherapy in the absence of bilirubin did not affect normal RBCs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Failure of phototherapy to be effective in reducing TSB levels in some infants with hereditary spherocytosis and hyperbilirubinemia has been hypothesized to be due to increased hemolysis from the absorption of light and photosensitization of cell membrane contents. In an in vitro study using RBCs from healthy donors and patients with hereditary spherocytosis, the investigators showed that the osmotic fragility of normal RBCs was increased in the presence of bilirubin or bilirubin and phototherapy 5. Phototherapy in the absence of bilirubin did not affect normal RBCs.…”
mentioning
confidence: 99%
“…Why does phototherapy fail in some patients with hereditary spherocytosis and hemolytic jaundice? In this month's issue, Bruzell Roll et al present three studies that shed some light on these areas 3–5.…”
mentioning
confidence: 99%